1985
DOI: 10.1148/radiology.154.2.3966142
|View full text |Cite
|
Sign up to set email alerts
|

A light-guidance system to be used for CT-guided biopsy.

Abstract: We describe a light-guidance system that uses intersecting helium-neon laser beams to provide precise guidance for biopsy approaches from any direction (including compound angles) during CT-guided biopsy of the chest and abdomen. Interactive software provides visualization of the proposed path, indicates the segment of that path that will pass through each section, and displays the settings for the apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
0
17
0
3
Order By: Relevance
“…Frederick et al [5] reported on a system that utilized planes of intersecting light to guide needle passage, and demonstrated an accuracy of ±1 mm and ±1°. Mechanical stereotactic devices have also been employed with good accuracy, resulting in a 75% decrease in needle manipulations in one study [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frederick et al [5] reported on a system that utilized planes of intersecting light to guide needle passage, and demonstrated an accuracy of ±1 mm and ±1°. Mechanical stereotactic devices have also been employed with good accuracy, resulting in a 75% decrease in needle manipulations in one study [6].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple systems and techniques have been developed to assist CT-guided procedures [5][6][7][8][9], varying from the complex (robotics) [1], to the simple fluid-filled disk, to approximate planned needle angulations [2].…”
Section: Introductionmentioning
confidence: 99%
“…The light localizer has previously been used in CT-guided biopsy procedures [4]. To our knowledge, the shadow cast by the hub of the needle over the point of entrance of the needle has not been used to correct the guidance of the needle as a substitute for fluoroscopy in fluoroscopically guided procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Laser guidance devices are also used to help guide probe placement in order to reduce procedure time and improve targeting accuracy [6]. Newer CT scanners, however, are often unable to tilt the gantry because of size and engineering challenges [7]. Consequently, there is a developing need for an alternative method of performing the double angled biopsies under CTguidance.…”
Section: Introductionmentioning
confidence: 99%